Action of gibberellic acid in roots. II. Pre-treatment action with gibberellic acid on the germination of sugarcane cuttings - Blesa, A. Carlos; Gómez, Manuel (Ars Pharmaceutica (Internet), 1967)
We have studied the effect that presowing treatments for 6, 12 and 24 hours, of sugar can cuttings had on cutting germination. We tested two pre-sowing treatments; with a control solution containing 0.2% ethyl alcohol and 2% of Sorbithom "TO" as wetting agent; and with a giberellic acid 10mg/l, solution also containing 0.2% ethyl alcohol and 2% Sorbithom "TO" as wetting agent. Our results clearly showed, that presowing treatments with the control solution stimulated root initiation, root growth and number, bur having no effect on shoot growth. However, when pre-sowing treatments were made with the gibberellic acid solution stimuli of root initiation, root growth and number were even higher that when control solution was used. Gibberellic acid increased also shoot growth to a great extend. The effect on roots were greater with 12 hours pre-sowing treatment but shoot growth was more stimulated with 24 hours pre-spwing treatments. Hos a good germination represents a good scope of an excellent yield, 12 hours pre-sowing treatments of sugar cane cuttings, mainly with a 10mg/l gibberellic acid solution, are recommended.